Students Error Analysis in Solving Mathematical Communication Problems of Square and Triangle Material For 7th Grade Based On Watson Criteria - Hunaifi, Hunaifi; Darhim, Darhim (International Conference on Elementary Education, 2020)
This study aims to analysis student errors in solving mathematical communication problem of square and triangles material based on error criteria according to Watson . The research design used was aqualitative descriptive study. The study was conducted in class VII junior high school in Subang with a total of 32 students . The instrument used in this study was a mathematical communication skills test in the form of a description of six questions that had been validated to one Mathematics Education lecturer and one mathematics subject teacher . The results of research in the form of answers of students in the identification based on Watson Watson criteria is obtained percentage of each category of inappropriate data (ID) of 5.72% , inappropriate procedure (IP) of 20.31% , lost data (ommited data/ OD) 9.89 %, omnited conclusion (OC) 17.69%, response level conflict (RLC) 1.56%, indirect manipulation (UM) by 4.16%, skills hierarchy problem (skills hierarchy problem/ SHP) 10.93% , and in addition to the seven categories above (above other/AO) of 44.26%. Based on this percentage it was found that in categories other than the seven categories above (AO) were the most common errors made bystudents